2005
DOI: 10.1007/s00467-005-2025-3
|View full text |Cite
|
Sign up to set email alerts
|

High-dose mizoribine therapy for childhood-onset frequently relapsing steroid-dependent nephrotic syndrome with cyclosporin nephrotoxicity

Abstract: Cyclosporin A (CsA) is an effective treatment for frequently relapsing steroid-dependent nephrotic syndrome (FR-SDNS), but its use can be complicated by renal toxicity and a high incidence of relapses after withdrawal. We report 9 adolescent patients with childhood-onset FR-SDNS who had been treated with long-term CsA that resulted in moderate-to-severe CsA nephropathy (CsAN). They were treated with high-dose (mean: 10.1 mg/kg per day) mizoribine (MZR) in an attempt to allow weaning of CsA and/or steroid thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 21 publications
(27 reference statements)
2
29
0
Order By: Relevance
“…24 On the other hand, we have successful experience with high dose mizoribine (mean 10.1 mg/kg/day) for children with steroid dependent who are also CsA dependent. 25 This therapy reduced CsA exposure and relapse rates. Furthermore, the multivariate analysis also revealed that an age younger than 5 years at the start of CsA treatment was another independent risk factor for CsAN.…”
Section: Discussionmentioning
confidence: 99%
“…24 On the other hand, we have successful experience with high dose mizoribine (mean 10.1 mg/kg/day) for children with steroid dependent who are also CsA dependent. 25 This therapy reduced CsA exposure and relapse rates. Furthermore, the multivariate analysis also revealed that an age younger than 5 years at the start of CsA treatment was another independent risk factor for CsAN.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the effects of mizoribine on the intracellular energy balance and nephrin biogenesis were observed at clinically attainable concentrations. [51][52][53] A better understanding of the pathomechanism of NS and the mechanisms by which antiproteinuric agents lead to remission in NS may allow development of new therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary data from a series of pediatric (1)(2)(3)(4)(5)(6)(7)(8) and adult (9 -11) studies suggest that mycophenolate mofetil (MMF) may represent a less toxic alternative for patients with FRNS. Other recent studies have reported that mizoribine (12)(13)(14)(15)(16)(17) or levamisole (18) also may be options to consider in such patients.…”
mentioning
confidence: 99%